Pengaruh Social Media Marketing Ms Glow Terhadap Loyalitas Konsumen (Survei Pada Followers Instagram @msglowbeauty - Karen Elissa Anindya; Velda Ardia (STIKes Ibnu Sina Ajibarang, 2024)
Social media is one of the marketing tools that can be used by businesses to get the attention of their consumers. Social Media Marketing is a strategy used by companies and has the aim of attracting consumer attention by obtaining a wider target market. So the purpose of this study is to determine whether Social Media Marketing has an influence on Consumer Loyalty. The theory used in this study is the theory of Social Media Marketing including, Online Communities, Interaction, Sharing of Content, Accessibility, Credibility and the theory of Consumer Loyalty which includes repeat, retention, referalls. This research uses quantitative methodology with survey method. The population used in this study were followers of the @msglowbeauty Instagram account who had made purchases on Ms Glow products more than 2x. The technique used was simple random sampling with a sample size of 80 respondents. The results of this study indicate the average value of respondents' answers to the variable (X) of 4.23, this value is classified as high (Agree) and the average respondent's answer to the variable (Y) of 4.54 which is also predominantly high (Agree). A considerable influence can be seen from the correlation (R) value of 0.795 which is arguably high or strong and the R Square value of 0.631 or 63.1% of the effect while the remaining 36.9% is influenced by other things.